An insight into the Chinese traditional seafood market: Species characterization of cephalopod products by DNA barcoding and phylogenetic analysis using COI and 16SrRNA genes. (December 2017) - Wen, J.; Tinacci, L.; Acutis, P.L.; Riina, M.V.; Xu, Y.; Zeng, L.; Ying, X.; Chen, Z.; Guardone, L.; Chen, D.; Sun, Y.; Zhao, J.; et al.
Abstract: Squids, cuttlefish and octopus are used for the preparation of traditional products sold on the Chinese market without a specific denomination. In this study DNA barcoding and phylogenetic distance analysis of COI and 16S rRNA genes' fragments were used to characterize the most commonly processed species in dried whole, grilled shredded and salted cephalopod preparations. Ninety-five products (23 sold as cuttlefish, 4 as octopus and 68 as squid) purchased in Chinese local markets were analyzed. Overall, the study identified 10 different species: Sepia pharaonis, S. esculenta, S. recurvirostra, S. lycidas in cuttlefish; Amphioctopus marginatus in octopus; Uroteuthis chinensis, U. edulis, Ommastrephes bartramii, Illex argentinus and Dosidicus gigas in squids. This latter species, characterized by a low commercial value, was found in the majority of the samples (50.5%) and in all the shredded products. By comparing the molecular results with the declared macrocategory (cuttlefish, octopus and squid), two cases of misdescription were pointed out, involving shredded cuttlefish and octopus which were identified as D. gigas . Our results are of particular interest in the light of the scarcity of data regarding the identification of cephalopods on international markets and considering that China is one of the leading cephalopod-producing countries. Highlights: Traditional Chinese squid, cuttlefish and octopus products were molecularly characterized. DNA barcoding and phylogenetic distance analysis on COI and 16S rRNA genes were used. Ten different species were found, locally sourced and imported from South America. Dosidicus gigas was the most represented species, constituting all shredded squids.